TEACHERS’ EFFORTS IN BUILDING STUDENTS’ CHARACTER IN LEARNING ENGLISH AT THE EIGHTH GRADE OF SMP NEGERI 2 HILIDUHO IN 2023/2024 - Hulu, Rasni; Telaumbanua, Yasminar Amaerita; Waruwu, Yaredi; Harefa, Afore Tahir (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2025)
Character education is a systematic approach to encourage the development of positive character traits and virtues in individuals, usually in an educational setting. The purpose of this research is to find out the teachers’ efforts in building students’ character and to find out the causes of students' poor character in Learning English. The method used in this research is qualitative analysis. The instruments in this research are interviews and observations. Data was obtained from interviews with English teachers to find out the teachers’ efforts in building students’ character and analyzing what indicators values have been implemented by teachers in the classroom while teaching. After analyzing teachers’ efforts in building students’ character in learning English through interviews and observations, the researchers found that both English teachers at SMP Negeri 2 Hiliduho have efforts in building students’ character, namely by inviting students to worship before the subject started, reviewing previous lesson to build students’ communicative value, providing opportunities for students to ask questions to build students’ curiosity value. However, in applying character indicator values to students, of 34 indicator values, teachers have applied 27 indicators to students, and 5 indicators have not been applied by both teachers and 2 indicators have not been applied by either teacher However, both English teachers have made good efforts in building students' character in learning English, so that the values applied have become a habit for students at SMP Negeri 2 Hiliduho in the eighth grade.